Income Comparisons among Neighbours and Life Satisfaction in East and West Germany - Gundi Knies (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
A series of studies have suggested that changes in others' income may be perceived differently in post-transition and capitalist societies. This paper draws on the German Socio-economic Panel Study (SOEP) matched with micro-marketing indicators of population characteristics in very tightly drawn neighbourhoods to investigate whether reactions to changes in their neighbours' income divide the German nation. We find that the neighbourhood income effect for West Germany is negative (which is in line with the "relative income" hypothesis) and slightly more marked in neighbourhoods that may be assumed to be places where social interactions between neighbours take place. In contrast, the coefficients on neighbourhood income in East Germany are positive (which is consistent with the 'signalling' hypothesis), but statistically not significant. This suggests not only that there is a divide between East and West Germany, but also that neighbours may not be a relevant comparison group in societies that have comparatively low levels of neighbouring.
Keywords: I31; C23; Z1; 330; Comparison income; Reference group; Life Satisfaction; Neighbourhood effects; Einkommen; Soziale Gruppe; Vergleich; Wohnstandort; Systemtransformation; Zufriedenheit; Deutschland; Ostdeutschland; Westdeutsche Bundesländer